Effects of Aging on Compressive Strength of Two Resin-Reinforced Glass Ionomers: An In-Vitro Study - M Emami Arjomand; MH Eghlim; SH Jalalian; M Mirzakhani; A Mahavi (Islamic Azad University, 2019)
Background and Aim: Although the physical properties of modern glass ionomers have been extensively reported, few studies have examined how these parameters change with age. This experimental study aimed to investigate the effect of aging on the compressive strength of resin-reinforced glass ionomers. Material and Methods: Two glass ionomers (Fuji IX GP Fast, GC, Japan, and Ketac Universal, 3M, USA) and one composite resin (control; Filtek P60, 3M, USA) were chosen for this study. Both glass ionomers were encapsulated and mixed using an amalgamator and were applied using an appropriate applicator. Forty cylindrical (4×6 mm2) samples were made of each material and subsequently incubated at 37°C with 95±5% humidity. Twenty samples from each material were then randomly selected to undergo aging in a thermocycling machine using 1000 cycles (between 5-55°C). The compressive strength of the samples was then measured using a universal testing machine. One-way analysis of variance (ANOVA) and post-hoc Tuckey's test were used for data analysis. Results: The aging process (thermocycling) caused a significant increase in the compressive strength of all three materials. Overall, Ketac Universal displayed higher compressive strength with an average value of 271.1120±15.4387 MPa and 248.6910±15.10716 MPa with and without aging, respectively, compared to Fuji IX GP and Filtek P60.     Conclusion: The aging process increases the compressive strength of glass ionomers and composites; however, even with aging, modern glass ionomers still struggle to achieve compressive strength values close to those feasible with composite resin. It is therefore essential to use these materials in non-stress-bearing areas.